2016
DOI: 10.1051/0004-6361/201628333
|View full text |Cite
|
Sign up to set email alerts
|

Applying the expanding photosphere and standardized candle methods to Type II-Plateau supernovae at cosmologically significant redshifts

Abstract: Based on optical imaging and spectroscopy of the Type II-Plateau SN 2013eq, we present a comparative study of commonly used distance determination methods based on Type II supernovae. The occurrence of SN 2013eq in the Hubble flow (z = 0.041 ± 0.001) prompted us to investigate the implications of the difference between "angular" and "luminosity" distances within the framework of the expanding photosphere method (EPM) that relies upon a relation between flux and angular size to yield a distance. Following a re-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…The EPM provides estimates of distance independent of extragalactic distance ladder. The method requires high-quality spectroscopic and photometric monitoring of SNe and was applied mostly to nearby objects (e.g., Hamuy et al 2001;Takáts & Vinkó 2006;Jones et al 2009;Bose & Kumar 2014), although recently it became possible to perform the EPM on SNe at cosmologically significant redshifts (e.g., Gall et al 2016Gall et al , 2018. The other method for distance determinations using SNe II-P is the Standardized Candle Method (SCM) (Hamuy & Pinto 2002), based on a correlation between the luminosity and the expansion velocity of SNe during the plateau phase.…”
Section: Introductionmentioning
confidence: 99%
“…The EPM provides estimates of distance independent of extragalactic distance ladder. The method requires high-quality spectroscopic and photometric monitoring of SNe and was applied mostly to nearby objects (e.g., Hamuy et al 2001;Takáts & Vinkó 2006;Jones et al 2009;Bose & Kumar 2014), although recently it became possible to perform the EPM on SNe at cosmologically significant redshifts (e.g., Gall et al 2016Gall et al , 2018. The other method for distance determinations using SNe II-P is the Standardized Candle Method (SCM) (Hamuy & Pinto 2002), based on a correlation between the luminosity and the expansion velocity of SNe during the plateau phase.…”
Section: Introductionmentioning
confidence: 99%
“…A direct comparison of EPM and SCM has been presented for nearby supernovae (Olivares et al 2010) demonstrating that both methods provide similar distances within the respective uncertainties. At cosmological distances, such a comparison will be a direct test of general relativity as a metric theory of gravitation (Wagoner 1977;Gall et al 2016). Gall et al (2016) demonstrated an extension to higher redshifts, albeit not yet at the cosmologically interesting level, for both methods for a single supernova (SN 2013eq at z D 0:04).…”
Section: Normalized Plateau Luminosity ("Standardized Candle Method")mentioning
confidence: 99%
“…At cosmological distances, such a comparison will be a direct test of general relativity as a metric theory of gravitation (Wagoner 1977;Gall et al 2016). Gall et al (2016) demonstrated an extension to higher redshifts, albeit not yet at the cosmologically interesting level, for both methods for a single supernova (SN 2013eq at z D 0:04).…”
Section: Normalized Plateau Luminosity ("Standardized Candle Method")mentioning
confidence: 99%
“…Quite interestingly, the two methods can give consistent results, up to cosmological distances (e.g. Gall et al, 2016).…”
Section: Introductionmentioning
confidence: 96%